Successful management of pregnancy in Turner syndrome (Monosomy X): A rare condition-based learning experience from Vietnam - Ngoc Bich Trinh; Anh Dinh Bao Vuong; Phuc Nhon Nguyen (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Turner syndrome (TS) is recognized with partial or complete loss of the second sex chromosome, occurring in approximately one in 2500 live births, and related to high failure of pregnancy. However, along with the advantage of assisted reproductive technology, the cases of TS pregnant women have been recently addressed worldwide. Therefore, the reproductive health of TS pregnant women should be a concern by physicians and obstetricians, particularly, in the low-middle income countries with low-resource settings. Case Presentation: Here, we describe a rare case of term pregnancy on a TS woman (45, XO) receiving oocyte donation at a private fertility center. Later, the woman was monitored uneventfully during antenatal care and hospitalized at our center for a cesarean delivery with favorable pregnancy outcomes at term. Conclusion: To our knowledge, this is the first report relating to a particular pathology in Vietnam. Through this case report, we would like to emphasize the novel opportunity for TS women desiring parents, thus raising an appropriate awareness of healthcare providers.